Sedimentation rate and coastal livelihood vulnerability a study of Manicani Island, Guiuan, Eastern Samar - Paa, John Paul E.
Knowledge, Attitude, and Practice (KAP) surveys reveal that local respondents' understanding of coastal and marine resources is rooted in experiential learning. The community demonstrates a favorable disposition towards environmental conservation, recognizing the ecological and economic benefits provided by marine resources (Spearman's rho, rs=0.05). Future research should focus on monitoring sedimentation rates and heavy metal concentrations in water and sediment, particularly post-initiation of mining activities. Comparative temporal studies are recommended to evaluate sedimentation across dry and wet seasons. Additionally, socio-economic assessments should consider the mining company's willingness to invest in environmental sustainability.